Psychological Aspects in Early Adjustment After Severe Burn Injury - Sirancova, Katarina; Raudenska, Jaroslava; Zajicek, Robert; Dolezal, Daniel; Javurkova, Alena (Journal of burn care & research, 2022)
Burn injury is one of the most serious traumatic events with possible psychological and psychosocial consequences. Health status perception is one of the main health outcomes. The severity of psychological symptoms does not always correlate with that of the burn injury, suggesting that early screening for psychological vulnerabilities may be beneficial. The aim of our study was to identify the personality, clinical, and sociodemographic characteristics related to patient's subjective perception of health, depression, and anxiety in a sample of 52 adult patients with severe burn injury shortly before discharge from specialty burn clinic. Subjective health perception was predicted by depression (β = -.143, t(47) = -3.94, P < .001) and neuroticism (β = -.106, t(43) = -4.83, P < .001), and it correlated positively with extraversion (r = .2858, P = .0465) and conscientiousness (r = .3663, P = .0096). Depression was predicted by neuroticism (F(1,49) = 18.4; P < .001) and correlated with attachment avoidance (r = .29, P = .0383) and negatively with extraversion (r = -.32, P = .0220). Anxiety was related to attachment anxiety (F(1,49) = 4.25; P = .045), neuroticism (F(1,49) = 15.75; P < .001), and agreeableness (r = -.36, P = .0101). Unemployed patients experienced higher levels of depression and anxiety. This research suggests that personality traits and adult attachment may play an important role in the acute phase of the recovery from a severe burn injury. These findings can be relevant for early intervention and holistic rehabilitation.
Keywords: Adaptation, Psychological; Humans; Unemployment; lidé středního věku; Burns; Female; rizikové faktory; nezaměstnanost; popálení; lidé; duševní poruchy; ženské pohlaví; stupeň závažnosti nemoci; Male; Middle Aged; adaptace psychologická; Mental Disorders; Severity of Illness Index; mužské pohlaví; Risk Factors